AN INTERNATIONAL TAXATION AND AGREEMENTS TO AVOID DOUBLE IMPOSITION - Santa Cruz Miranda, Adolfo (2014)
The Peru, develops from about 20 years ago macroeco-nomic policy of opening up to international capital, the export of primary products and the promotion of goods subject to a production process that will generate an exportable and competitive value added in the world market. In this context, is a “state policy” subscription “international agreements” that allow us to complement our macroeconomic policies and agree with other countries, and the study, assessment and resolution of their tax effects, in the search for legal certainty to foreign investment and competitiveness of our value-added production, looking at the world as a target.This work analyzes and explains the causes of interna-tional juridical double taxation, which originated in their tax effects corrective established in CDI. Because of this, we apply ourselves the analysis and comments on the purpose and scope of the framework agree-ments to avoid double taxation, our country has been used as prototypes to suit, negotiate and eventually sign agreements with third countries. The Framework Convention’s used by our country is the OECD Model (Organization for Economic Cooperation and De-velopment), an agency of the so-called “Group 20”, where the main countries in wich the world is found. The second framework convention is that developed by the United Nations. Both “framework agreements” have different scopes, they also analyzed, while using different criteria to determine the country to which it falls to tax income.